Socio-economic role and institutional capacity of family farms in the implementation of the sustainable development goals - Kyfyak, Viktoria; Lopatynskyi, Yurii; Shpykuliak, Oleksandr; Shelenko, Diana; Diuk, Anna (EKONOMIKA APK, 2023)
Rapid changes and dynamic fluctuations in modern social development determine the relevance of institutional transformations in the implementation of proclaimed sustainable development goals. In achieving this, the socio-economic role of effectively reaching the institutional potential of family farms increases. The purpose of the paper is to detail methodological judgments and develop parameters for determining the institutional potential and socio-economic role of family farms in the implementation of the United Nations sustainable development goals for the period up to 2030, considering national economic characteristics. In achieving the purpose, a systematic approach and theoretical (axiomatic, analysis and synthesis, analogies) and empirical research methods (comparison, expert assessments) were applied. The obtained results provide deeper methodological insights and characterisation of the socio-economic and institutional role of family farming in the national economy and sustainable development goals. Family farms play a creative role in maintaining a balance between meeting the population's needs and efficient utilization of agricultural potential. The paper presents an original interpretation of the category “institutional potential” of family farms. Institutional potential can be defined as the capacity of institutions to maintain stability and conditions conducive to fulfilling their functions, influencing the behaviour of social actors. It also involves delineating and differentiating the socio-economic and institutional characteristics of family farming. The study also substantiates economic, social, and nvironmental factors affecting the development of family farming concerning their role in achieving sustainable development goals. The necessity of making managerial decisions at various levels to increase the level of sustainability of the agri-food system was noted. The practical value of the study is provided by methodological generalisations, consolidation of knowledge, and confirmation of theoretical conclusions about the features of the functioning of family farms in the context of proving the objectivity of their socio-economic role and the effectiveness of using institutional potential in the implementation of sustainable development principles
Keywords: entrepreneurship; sustainable development principles; food security; institutions